Targeted anti-cancer effects of Octomeles sumatrana on colorectal cancer cells - Suhaini Sudi; Nurfazlin Ismail; Siti Nureza Lahaba; Nur Atikah Anuar; Wenne Junarsi Rozana William; Siti Yasmin Mohd Ikmal Hisham; Syarifah A'eesyah Syed Shikh; Goh, Lucky Poh Wah; Eleanor Joanne Muyou; Caroline Sunggip (Faculty of Science & Natural Resources, UMS, 2024)
Colorectal cancer (CRC) continues to be a significant public health concern due to its high incidence and mortality rates. The exploration of bioactive natural compounds as adjuncts to traditional chemotherapeutic agents holds promise for improving treatment outcomes against CRC. This study investigates the selective anti-cancer properties of methanolic extract of Octomeles sumatrana (OS) on CRC cell line HCT15 and normal colon cell line CCD112, focusing on its anti-proliferative, antimigration, and anti-oxidative effects. Cytotoxicity was assessed using the MTT assay, revealing OS IC50 values of 8.37±0.92 μg/ml for HCT15 and 121.30±2.09 μg/ml for CCD112 cells. Comparatively, the control drug doxorubicin (Dox) exhibited IC50 values of 20.98±1.32 μg/ml for HCT15 and 6.14±0.79 μg/ml for CCD112, highlighting OS's superior selectivity (selectivity index: 14.5 for OS vs. 0.29 for Dox). OS significantly reduced the migration rate of HCT15 cells to 1.33% compared to 22.33% in untreated controls (p<0.05). Furthermore, intracellular superoxide detection using DHE dye indicated a marked reduction in oxidative stress in OS-treated HCT15 cells (p<0.05). These results suggest that OS selectively inhibits cancer cell proliferation, mitigates migration, and reduces oxidative stress, showing promise as an ethnomedicinal candidate for CRC treatment. The study emphasizes OS’s potential as a natural adjunct or alternative to conventional therapies, warranting further research into its bioactive compounds and mechanisms of action.